Pengaruh Perilaku Kepemimpinan, Budaya Organisasi, dan Motivasi Kerja terhadap Etika Kerja Guru Muhammadiyah Kota Pekan Baru Provinsi Riau - Zein, M. Rasyad; Sujanto, Bedjo; Hasri, Salfen (JERAM, 2018)
This research was motivated by the work ethics of teachers in Muhammadiyah schools that were not good yet, where loyality and compliance to organization is still low and there is less concern with the morality of the job. The aim of this research is to study the influence of leadership behavior, organizational culture, and work motivation toward the work ethics of Muhammadiyah teachers in Pekanbaru of Riau Province. This research has used a survey method with the causal technique. Meanwhile, to analyze the influence between variables the path analysis is used. The path analysis requires of a significant linear regression relationship between two variables. Meanwhile, to calculate the coefficient of each path, a positive correlation coefficient of two variables is required. The population in this research is Muhammadiyah teachers in Pekanbaru of Riau Province of totally 172 teachers and the sampling is 120 teachers. The results of this study indicate that there is; (1) a direct positive influence of leadership behavior toward teachers' work ethic, (2) a direct positive influence  of organizational culture toward teachers' work ethics, (3) a direct positive influence of work motivation toward teachers' work ethics, (4) a direct positive influence of organizational culture toward work motivation, (5) a direct positive influence of leadership behavior toward work motivation. Thus, the improvement of work ethics of teachers can be achieved well if there is a strong influence of leadership behavior, organizational culture and well organized work motivation. Keywords: work ethics, leadership behavior, organizational culture, and work motivation